Seed yield components of five cultivars of white clover - Franke, Lúcia Brandão (1991)
The field trial was conducted at the Estação Experimental Agronômica -UFRGS, Eldorado do Sul, RS, Brazil, to study the response of the seed yield components of five cultivars of white clover (Trifolium repens L.) named: BR-1-Bagé, Jacuí S2, Regal, Yi and Guaíba S1. The variables were measured weekly during two years. The experimental variables under study were: number of flower heads per area, number of flowers per flower head, seed weight, number of seeds per flower head, yield of seeds per flower head and yield of seeds per plot. The period around December 14 was considered as the best harvest time for white clover seed, for all cultivars in both years. The observed values for the second year were higher than those of the first year, irrespective of the clover cultivar except for number of flowers per flower head. The cultivars Guaíba S1 and Regal showed the greatest and lowest values, respectively for the majority of the experimental variables under study.